STUDYOFIIClandBr/ClloNExcHANGEEQUILIBRIAONLEWITATM500CHELAT- INGRESIN - Khalil, S A; Omar, M B (Biological Sciences - PJSIR, 2002)
Thermodynamic equilibrium constants of IICf and BrlCI ion exchange reaction on the strongly basic anion - exchanger Lewitat M500 were determined different temperatures ranging from 25°_- 45°C. It was found that the value of K is g and increases with increasing in temperature and K ris greater that K :,. The standard enthalpy Ml, free energy 6G oo 0 .J – and entropy 6S changes were calculated. 6H of ion exchange reactions were obtained to be 20.43 KJ mol for IICl and -I – 16.63 KJ mol for BrlC!.